“Localising Tropical Medicine”: A History of the Medical Research Institute (MRI) in Colonial Lagos, 1907–1920s - Adedamola Seun Adetiba (Modern Africa)
This article explores an early episode in the history of tropical medicine in colonial Lagos, British West Africa. It probes into the activities and outputs of scientists who operated within the Medical Research Institute (MRI) as a way to further complicate the agendas of tropical medicine. Scientists of the MRI undertook biomedical experimentation with a profound understanding of metropolitan and local imperatives as both determined the extent to which they contributed to popular discourses. The present paper explores the extent to which metropole-colony relations triggered local scientists at the MRI to resort to all available means, including human experimentation, in the course of ambitious scientific projects. In certain other contexts, international and local motivations converged to sway the ambivalent postures of colonial scientists to biomedical experimentation.